Long-term anti-inflammatory effects of injectable celecoxib nanoparticle hydrogels for Achilles tendon regeneration - Jun Kim; Seo Bo-Bae; Ki Hyun Hong; Kim S.E.; Kim Y.-M.; Song S.-C. (Elsevier BV, 2022)
The treatment of chronic Achilles tendonitis (AT) often requires prolonged therapy and invasive therapeutic methods such as surgery or therapeutic endoscopy. To prevent the progression of chronic AT, excessive inflammation must be alleviated at an early stage. Corticosteroids or nonsteroidal anti-inflammatory drugs are generally prescribed to control inflammation; however, the high doses and long therapeutic periods required may lead to serious side effects. Herein, a local injectable poly(organophosphazene) (PPZ) ？ celecoxib (CXB) nanoparticle (PCNP) hydrogel system with long-term anti-inflammatory effects was developed for the treatment of tendonitis. The amphiphilic structure and thermosensitive mechanical properties of PPZ means that the hydrophobic CXB can be easily incorporated into the hydrophobic core to form PCNP at 4 °C. Following the injection of PCNP into the AT, PCNP hydrogel formed at body temperature and induced long-term local anti-inflammatory effects via sustained release of the PCNP. The therapeutic effects of the injectable PCNP system can alleviate excessive inflammation during the early stages of tissue damage and boost tissue regeneration. This study suggests that PCNP has significant potential as a long-term anti-inflammatory agent through sustained nonsteroidal anti-inflammatory drugs (NSAIDs) delivery and tissue regeneration boosting. Statement of significance: In the treatment of Achilles tendinitis, a long-term anti-inflammatory effect is needed to alleviate excessive inflammation and induce regeneration of the damaged Achilles tendon. Injectable poly(organophosphazene)(PPZ)-celecoxib(CXB) nanoparticles (PCNP) generated a long-term, localized-anti-inflammatory effect in the injected region, which successfully induced the expression of anti-inflammatory cytokines and suppressed pro-inflammatory cytokines, while the PCNPs degraded completely. Accordingly, regeneration of the damaged Achilles tendon was achieved through the long-term anti-inflammatory effect induced by a single PCNP injection. The PCNP system therefore has great potential in long-term NSAIDs delivery for various tissue engineering applications.